Laboratory and field monitoring tests of volcanic soil (Ta-d) triggering landslides in the 2018 Hokkaido Eastern Iburi earthquake - Kimika Kawamura; Satoshi Matsumura; Shima Kawamura (Geoenvironmental Disasters)
Abstract Background The 2018 Hokkaido Eastern Iburi Earthquake triggered serious geodisasters, resulting in several landslides in volcanic soils depending on their geological features. However, there is limited investigation from the geotechnical viewpoint. Considering various volcanic soils are deposited in Hokkaido, Japan, it is crucial to ensure disaster prevention of infrastructures related to volcanic soils. Methods To investigate the degree of weathering, water-retention characteristics, and mechanical properties of the volcanic soil, which triggered landslides during the earthquake, called Ta-d, this study conducted laboratory tests including X-ray diffraction, water-retention, and direct shear tests under various conditions related to a type of Ta-d, saturation condition, and stress dependency. Moreover, the pore pressure of the location where the landslides occurred was monitored for over a year to investigate the effect of rainfall on the previous day of the earthquake on the landslides. Results The laboratory and field monitoring test results showed that Ta-d can be categorized into three types depending on the color and physical properties, which have different degrees of weathering and shear strengths. The water content of Ta-d was high (>100 %) throughout the year, whereas it exhibited a seasonal change due to snowfall, which covered the ground surface. Furthermore, fluctuations caused by the seasonal changes are more significant than those caused by rainfall, which indicated that the rainfall on the previous day of the earthquake was not a primary factor in the occurrence of the landslides Conclusions This study reveals the geotechnical properties of Ta-d, which has not been well known, as comparing with those of other Hokkaido volcanic soils, and gives insights into the significant factors that can potentially cause the earthquake-induced geodisasters.